Implementing Phone Coaching Method in Promoting Healthy Lifestyles among Malaysian - Mohd. Hashim, Asha Hasnimy; Zainuddin, Zainal Abidin; Ibrahim, Halijah (2006)
There are numerous of health benefits accrued as a result of regular physical activity participation are well documented and include improvements in either physiological and psychological health status or known by quality of life. However, despite these benefits, some people fail to adopt physically active lifestyle. There are many strategies in applying physically activity for health promotion. This involves phone coaching. Study from Curtis et. al. (2003) shows that phone coaching helps coached group increasing their daily physical activity by 52.4% compared to control group after four weeks of observation. Therefore, due to the incoming of mobile phone usage among Malaysian increase dramatically every year, we suggest to use phone coaching as alternative to promote healthy lifestyles among Malaysians.